Effect of three sources of fibre and period of feeding on the performance, carcass measures, organ relative weight and meat quality in broilers (2005)
One hundred and fifty male broilers were used in a 3 x 3 factorial design to evaluate the effect of 3 periods (4, 8 and 12 weeks) and 3 fibre sources namely; brewer’s dried grain (BDG), palm kernel meal (PKM) and corn bran (CB) in place of maize on the performance, carcase measures and meat quality in the birds. A sensory evaluation to determine the overall acceptability of the meat was also carried out. Four diets were formulated consisting of a basal diet containing none of the test fibre ingredients. In the remaining 3 diets, either of BDG, CB or PKM was used to replace 40% of the maize. A separate balance study was also carried out to determine the digestibility of nutrients in the birds. BDG, CB and PKM significantly (p<0.01) reduced the weight and feed conversion in the birds but period of feeding resulted in increased body weights of the birds. BDG, CB and PKM significantly (p<0.01) reduced the eviscerated weights and the weights of carcase parts but period significantly (p<0.01) increased them. Dietary treatment, period and their interaction significantly (p<0.01) reduced the abdominal fat in the birds and caused a significant (p<0.05) increase in the lengths of the duodenum, ileum, caecum and colon as well as the weight of the intestines. Digestibility of nutrients was significantly (p<0.1) reduced in birds on the fibre diets. The shear force values in carcase parts were significantly increased in the BDG, CB and PKM diets while the cooking loss was significantly (p<0.05) reduced in these diets. Period and interaction with dietary treatment also caused a significant (p<0.01) reduction in cooking loss. Tenderness, flavour and juiciness were significantly (p<0.01) influenced by period and not treatment but overall acceptability of the meat was significantly (p<0.05) increased by both factors. Results of the study suggest 1) 40% BDG, CB and PKM replacement of maize has a negative effect on the weight gain and feed conversion of broilers, 2) 40 % level of BDG, CB and PKM caused an increase in the weights and lengths of the visceral organs and reduced carcase weight in broilers, 3) production of broilers up 10-12 weeks on 40% BDG, CB or PKM diet resulted in creased flavour, juiciness, higher shear force, reduced tenderness, reduced cooking loss but increased general acceptability of broiler meat.